Obesity, income and gender: The changing global relationship - Hannah Ameye; Johan Swinnen (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2019)
Obesity is considered one of the major health concerns of the 21st century and is frequently associated with economic development. This paper reviews evidence on internal (within countries) and external (across countries) relationships between obesity, income and gender. Obesity changes with income, but in a non-linear way. On average, obesity increases with income in poor countries, has no relationship with income in middle-income countries and decreases with income for rich countries. Within countries, obesity is concentrated among richer groups in low-income countries and evenly distributed in middle-income countries. In high-income countries, the poor are the most obese. The relationship differs for men and women. Women are more obese in low-income countries and much more obese in middleincome countries. The gender obesity gap disappears in high-income economies. The geographic concentration of obesity also changes with income growth: from urban areas in poor countries to rural areas in rich countries. Despite these patterns, total obesity rates continue to increase in all countries, and for the world as a whole.
Keywords: 330; Obesity; Income; Gender; Urbanization